SAT0054 Clinical efficacy and safety of loxoprofen sodium in the treatment of gonarthrosis. (1st June 2001) - Lederman, R; Guimarães, S; Verztman, JF
Abstract : Background: There have been advances in the understanding of osteoarthritis, but current treatment is purely to control symptoms. NSAIDs drugs remain the most commonly used agents, despite their potential for GI adverse events. Loxoprofen sodium, a NSAID prodrug from phenylpropionic class, synthesised by Sankyo Co., is claimed to have lesser GI and renal toxicity, probably due to its prodrug characteristics and to intermediate COX-2 selectivity. A large clinical experience in oriental people is available, but its use in occidental people is scarce. Objectives: The objective of this double blind, randomised, parallel, controlled trial was compare the efficacy and safety of Loxoprofen with that of diclofenac in the treatment of gonarthrosis. Methods: Ambulatory patients with gonarthrosis grade 2 or 3 of Kellgren and Lawrence classification, 30 ? 60 years old, with body mass index (BMI) < 30 kg/m 2 were admitted to the study after comply with inclusion and exclusion criteria. After have been given their informed consent, patients were randomly allocated, in a double-blind way, into treatment groups – Loxoprofen 60 mg t.i.d. or diclofenac 50 mg t.i.d. Duration of treatment was four weeks, and patients were evaluated at pretreatment and every two weeks during therapy for: overall severity of symptoms; pain at rest, on pressure, on movement and nocturnal through a visual analogue scale (VAS); swelling of knee; functional disability; global improvement; side-effects. Laboratory tests were performed in all patients, pre and post treatment. Results: A total of 60 patients was treated ? 30 in each group. There was no significant difference between the groups; 87% of patients were >51 years old. Mean disease duration was 2655 ± 2168 days in LOX and 2086 ± 1333 days in DIC (n.s.). 23 patients in LOX and 24 in DIC reported previous treatments with NSAIDs, being diclofenac the most frequent prescribed drug. All parameters evaluated showed statistically significant improvements compared with baseline (p < 0.0001 ? chi square) with both treatments; there were no statistically significance differences between treatments groups. GI adverse events occurred in 3 patients (10%) of LOX and in 12 (40%) of DIC(p < 0.01). Epigastralgia was the most prevalent GI event reported (1 in LOX; 7 in DIC). One serious adverse event ? enterorrhagia ? was reported in the diclofenac group, with discontinuation of treatment. Tolerability assessments were classified as both very good and good in 90% in LOX and in 79% in DIC (p < 0.05). One patient in LOX discontinued therapy due to worsening of the disease, and 5 in DIC ? 4 due to adverse events and 1 worsening of the disease. About 80% of overall assessment were classified, by investigator and patient, as either very good or good in Loxoprofen group and 70% in the diclofenac group (n.s.). Conclusion: Loxoprofen 60 mg, t.i.d., showed good efficacy accompanied by excellent tolerability and safety in gonarthrosis, which was superior to that of an established NSAID, diclofenac 50 mg, t.i.d.